Analisis Sistem Antrian Pelayanan Registrasi Mahasiswa di BAAK Universitas Tridinanti Palembang - Basuki, Mahmud (Jurnal Sistem dan Manajemen Industri, 2018)
Administrative Bureau of Academic and Student Affairs (BAAK) Tridinanti University of Palembang (UTP) is an institution that serves the academic administration and UTP student affairs. The approval of the KRS (Card Study Plan), the management of transcripts of grades, and the taking of diplomas are the requirements of the students at BAAK, so in the registration condition of the students, especially at the end of the registration period, there is a solid queue that the majority of the students need is the endorsement of KRS. One factor could be due to lack of servers (service personnel). The purpose of this study to determine the needs of the number of servers that should be used BAAK UTP using queue theory. The results showed that the condition of queue in solid condition, need to be added 1 server so that become 4 server, level of usage that is 79%.